The Illness Experiences of Adolescents with Type 1 Diabetes Mellitus: A Qualitative Meta-synthesis - Ziyu Sun; Wenjuan Zhang; Jiaqi Wang; Yibao Zhang; Yuhong Wu (Elsevier, 2024)
Summary: This study aims to systematically review the illness experience of adolescent patients with type 1 diabetes mellitus (T1DM). The JBI qualitative systematic review method was used and meta-aggregate analysis of 14 qualitative studies was performed. Qualitative studies on the disease experience of adolescent patients with T1DM were obtained from Cochrane, PubMed, Web of Science, CINAHL, Embase, Wanfang, CNKI, and VIP, and the search period was from 1995 to 2024. The qualitative research quality evaluation tool of JBI the Evidence-based Health Care Center in Australia was used to evaluate the analysis results. Thirty-one results were distilled and categorized into 7 themes and then synthesized into 3 overarching findings: (1) experiencing psychological distress and developing coping mechanisms following adjustment; (2) acknowledging self-management shortcomings and actively seeking support; and (3) overcoming challenges and growing through experiences. The findings illuminate that adolescents with T1DM often experience negative physical and emotional challenges during their illness. Transitioning from dependency to independence poses numerous obstacles that can be overcome by improving both internal and external support, cultivating self-management skills, strengthening coping mechanisms, and achieving control over the disease while fostering personal growth.